2013
DOI: 10.4103/0301-4738.105049
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional graft survival, 10 years after epikeratoplasty in keratoconus

Abstract: Purpose:To report outcomes of epikeratoplasty in keratoconus (KC), utilizing manually-prepared plano donor lenticules in terms of flattening of the cone, reduction in astigmatism and improvement in the visual acuity.Materials and Methods:Patients with KC, having visual acuity <20/200, astigmatism >12 diopters (D) but without corneal opacity underwent epikeratoplasty, using manually prepared plano donor lenticules from fresh or M.K preserved corneas, between 1990 - 2000 and followed for 10 years, were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…To the best of our knowledge, the longest follow-up duration of epikeratophakia for the aphakic eye was 28 years, as reported by Kang et al [4]. Studies by Spitznas et al [5] and Panda et al [6] reported follow-up durations of 7 and 10 years, respectively. Both reports showed good results with stable refraction and improved visual acuity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…To the best of our knowledge, the longest follow-up duration of epikeratophakia for the aphakic eye was 28 years, as reported by Kang et al [4]. Studies by Spitznas et al [5] and Panda et al [6] reported follow-up durations of 7 and 10 years, respectively. Both reports showed good results with stable refraction and improved visual acuity.…”
Section: Discussionmentioning
confidence: 87%
“…Epikeratophakia is a refractive surgical procedure in which corneal lenticule tissue from a donor is sutured into the patient's cornea. This procedure is used to correct aphakic eyes, hyperopia, and keratoconus [1][2][3][4][5][6]. Refractive correction is achieved by transplanting a corneal lamellar disk without corneal endothelium, which helps suppress corneal graft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the subsequent final refractive errors and higher-order aberrations may severely affect the visual outcome, even if the surgery is successful [ 31 ]. Epikeratoplasty seems to stabilize astigmatism in patients with keratoconus, suffering from intolerance of contact lens, irrespective of astigmatism and corneal thickness [ 32 ]. Post-operative complications such as, persistent epithelial defect (PED), severe anterior segment inflammation during early post-operative period, graft melting and interface haze during the intermediate post-operative period, hypoesthesia, peripheral corneal ulcer and posterior sub-capsular cataract during the late post-operative period, have been reported [ 33 - 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…В литературе описаны преимущества данного метода в сравнении со сквозной кератопластикой (СКП). К ним относят уменьшение операционного риска и иммунологических осложнений, ведущих к отторжению трансплантата [9,10]. Авторы сходятся во мнении о недостатках эпикератопластики, описывая слабо прогнозируемый конечный результат операции, снижение контрастной чувствительности, незначительную степень восстановления остроты зрения по сравнению с таковой при СКП [9,10].…”
unclassified